2019
DOI: 10.1111/maps.13290
|View full text |Cite
|
Sign up to set email alerts
|

Geology of the Morasko craters, Poznań, Poland—Small impact craters in unconsolidated sediments

Abstract: Confirmed small impact craters in unconsolidated deposits are rare on Earth, and only a few have been the subjects of detailed investigations. Consequently, our knowledge of indicators permitting unambiguous identification of such structures is limited. In this work, detailed geological mapping was performed in the area of the Morasko craters, of which the largest crater is of about 96 m diameter. These craters were formed in the mid‐Holocene (~5000 yr ago) in unconsolidated sediments of a glacial terminal mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 34 publications
(96 reference statements)
1
18
0
Order By: Relevance
“…The structures are listed as proven impact craters in the Impact Earth database, despite lack of commonly accepted, unequivocal proof of extraterrestrial collision identified at this location. We excavated trenches though the Ilumetsa Large and Ilumetsa Small structures and found small pieces of charcoal within the putative proximal ejecta in both structures, in a similar geological setting as previously identified charcoal in Kaali (Losiak et al 2016) and Morasko craters (see Szokaluk et al 2019). Our 14 C dating of charcoal allowed us to conclude that these crater-like features formed simultaneously between 7170 and 7000 cal.…”
supporting
confidence: 72%
See 4 more Smart Citations
“…The structures are listed as proven impact craters in the Impact Earth database, despite lack of commonly accepted, unequivocal proof of extraterrestrial collision identified at this location. We excavated trenches though the Ilumetsa Large and Ilumetsa Small structures and found small pieces of charcoal within the putative proximal ejecta in both structures, in a similar geological setting as previously identified charcoal in Kaali (Losiak et al 2016) and Morasko craters (see Szokaluk et al 2019). Our 14 C dating of charcoal allowed us to conclude that these crater-like features formed simultaneously between 7170 and 7000 cal.…”
supporting
confidence: 72%
“…), the Kaali 2/8 double crater (unpublished data based on 2016 fieldwork), and at the Morasko crater (Szokaluk et al. [, ] and field visits by AL) have been found to have ages consistent with independently determined ages of the formation of these craters. Despite the lack of obvious meteroritic evidence found in the region of the Ilumetsa structures, we show that charcoal is similarly distributed within proposed ejecta blanket of both Ilumetsa structures.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations